26.90 is the answer. hope this helps!
Answer:
1
Use the quadratic formula
=
−
±
2
−
4
√
2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}
x=2a−b±b2−4ac
Once in standard form, identify a, b, and c from the original equation and plug them into the quadratic formula.
2
+
5
−
2
=
0
x^{2}+5x-2=0
x2+5x−2=0
=
1
a={\color{#c92786}{1}}
a=1
=
5
b={\color{#e8710a}{5}}
b=5
=
−
2
c={\color{#129eaf}{-2}}
c=−2
=
−
5
±
5
2
−
4
⋅
1
(
−
2
)
√
2
⋅
1
Step-by-step explanation:
this should help
ya I want to go get back to the school and I will get back to school today I don’t have
The transformations are vertical translation 7 units up.horizontal translation 3 units to the left
We have given that the equations
let f(x)=x^2 and g(x)=(x-3)^2+7
We have to determine the correct transformation,
<h3>What is the vertical translation?</h3>
Vertically translating a graph is equivalent to shifting the base graph up or down in the direction of the y-axis. A graph is translated to k units vertically by moving each point on the graph k units vertically.
Notice that the addition of 2 units to the variable x in the exponent involves a horizontal shift to the left in 2 units.
Notice as well that subtraction of 4 units to the functional expression involves a vertical shift downwards in 4 units.
To learn more about the transformation visit:
brainly.com/question/2689696
#SPJ1
I think it's 112 I did it in my head might be wrong